Understanding Chinese Heritage Language Teachers in Finland : experiences, challenges, and professional development needs - Wang, Lili (My University, 2022)
The professional development of heritage language teachers has gained much attention in recent years. However, in Finland, a few studies have been conducted about students and parents, but the studies about HL teachers' profile and their professional development are rare. Thus, this study aims to investigate a specific group of heritage language teachers, their background, teaching experiences, their interest and need for future professional development. This study adopted both quantitative and qualitative methods, more specifically, an online survey(n=10) and semi-structured interviews (n=5) were utilized as the research tools. Finally, the result presented the general situation of CHL instruction in Finland and followed by the recommendations for the stakeholders in the CHL program.
Keywords: heritage language, Chinese heritage language, heritage language teachers, Chinese heritage language teachers, teacher development